Blood Diamonds: The Successes and Failures of the Kimberley Process Certification Scheme in Angola, Sierra Leone and Zimbabwe - Audrie Howard (Washington University Global Studies Law Review, 2015)
Over the past several decades, diamond trade has fueled conflicts in many countries across the world. The Kimberley Process Certification Scheme, implemented in 2003, sought to “eliminate the presence of conflict diamonds in the chain of producing, exporting and importing rough diamonds” within participating countries. Some have considered the Kimberley Process Certification Scheme a success while others view it as a strong attempt at resolution that has ultimately failed. There are also many proposals for changes and additions to the existing structure that aim to make the KPCS more effective. This Note will focus on the history of the blood diamond trade in three African countries: Angola, Sierra Leone, and Zimbabwe. The Note will delve into the history of blood diamonds in these three countries, including the conflicts which have been fueled by diamonds, and may still be fueled by diamonds today. Further, it will detail the history of the KPCS—its structure regarding membership and policy, how it works, and how it is enforced and implemented in the three countries. Finally, the Note will examine some areas where the KPCS is lacking as well as some proposed revisions to make the KPCS more effective. Lastly, this Note will evaluate how the KPCS should realistically and practically be updated to accommodate for changes in the realm of the diamond trade.
Keywords: blood diamonds; Kimberly Process Certification Scheme; international law